MODEL KOMUNIKASI ANTARA ORANG TUA DAN REMAJA TENTANG KESEHATAN REPRODUKSI - Ismiyati, Ismiyati; Rumiatun, Darti (JURNAL MEDIA KESEHATAN, 2019)
Kematian remaja usia 15-19 tahun disebabkan adanya permasalahan dalam kesehatan reproduksi seperti komplikasi kehamilan, perdarahan, sepsis, persalinan terhambat, komplikasi pada aborsi yang tidak aman, penyakit seksual, serta penyalahgunaan obat-obat terlarang. Untuk mengatasi hal tersebut, mereka akan mencari informasi dari media, teman sebaya, dan orang tua. Namun, kenyataan yang ada pada saat ini adalah banyak remaja yang tidak mendiskusikan kesehatan reproduksi kepada orang tuanya. Alasan orang tua tidak berbicara dengan remaja tentang seksualitas dan kesehatan reproduksi salah satunya adalah kemampuan komunikasi yang masih kurang dalam kesehatan reproduksi. Untuk mengatasi permasalahan ini maka dilakukan penelitian untuk membangun model pendekatan komunikasi efektif tentang kesehatan reproduksi untuk orang tua ke remaja. Death of adolescents aged 15-19 years of differences in reproductive health complications such as pregnancy complications, bleeding, sepsis, obstructed labor, complications in unsafe abortion, sexy diseases, and the use of illegal drugs. To overcome this, they will seek information from the media, peers, and parents. However, the challenge at this time is that many teenagers do not discuss health for their parents. The reason parents don't talk to teens about sexuality and health is one that supports communication that is still lacking in reproductive health. To overcome this problem, research is conducted to build a model that discusses effective communication for parents. This study uses a constructive paradigm with qualitative methods with a sound foundation of theory to understand effective communication models between parents and adolescents in discussing the health of accepting adolescents. The results of this study found a communication model between parents and adolescents. When discussing with corpses, parents need to be debated by overcoming adolescent challenges and needs. Besides, parents also need to make good interactions so that trust emerges between the two. Communication requires knowledge, skills, and attitudes from parents so that adolescents can be open with their problems. To facilitate information, parents can use the media. Parents also need to argue about what works when they talk or discuss freedom.